A Dynamic Network Approach for E-Learning Based Electronics Virtual Lab to Mitigate COVID-19 - Nassef, Tamer M.; Haggag, Ayman; Nessim, Sameh; Yousry, Alaa; Aboshosha, Ashraf (Journal of Risk and Crisis Management, 2020)
During the pandemic spread of COVID-19, it is very essential to develop modern and technology-based alternatives for traditional education. Virtual laboratories promote education and will be used in the future as the primary instructional instruments. Learning in a virtual laboratory minimizes teachers’ worries about time, expenses, or hazards involving choosing improper, ineffective, or possibly harmful experimental approaches and fulfills the urgent need for social distancing to avoid the spread of infectious diseases. It offers higher student-to-component interaction and perception. Learning in a virtual lab enables more data to be obtained. The purpose of this research study is to train the student for practical application and experiment with measuring tools such as voltmeters and data acquisition systems. The student can also compare two outputs: the first is the outcome of the actual scheme, and the second is the virtual signal, the pure sine wave that can be regulated by frequency, amplitude, and phase. It can also send and obtain information from the teacher to the student. The teacher can see and follow up on what the learners are doing, so the teacher can better regulate the classroom. Experimental results show the superiority and the success of our proposed method in enhancing students’ learning experience.